A bismuth-based superconducting alloy and a method for producing the same

CN123002894APending Publication Date: 2026-10-30ZHUZHOU KENENG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611002569.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]本发明的第二个目的在于提供一种铋基超导合金的制备方法,本发明通过成分梯度调控与低温烧结的协同,有效解决成分均匀性差、烧结温度高、Bi挥发严重、无功能梯度设计的技术问题,实现铋基超导合金的低能耗、低成本、高性能制备

Benefits of technology

[0040]1. 超导性能显著跃升:通过三维成分梯度设计,实现了芯部高载流、表层高磁通钉扎、界面高结合力的功能一体化,所得铋基超导合金为Bi-2223相,零电阻临界温度T_c达108-110K,77K、1T条件下的临界电流密度J_c≥2×104 A/cm²,磁通钉扎力提升50%,磁场下J_c衰减降低40%,满足高端超导应用需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002894A_ABST
    Figure CN123002894A_ABST
Patent Text Reader

Abstract

The application discloses a bismuth-based superconducting alloy and a preparation method thereof. The bismuth-based superconducting alloy has a symmetrical gradient structure from top to bottom, that is, an upper surface layer, an upper transition layer, a core layer, a lower transition layer and a lower surface layer. The content of Bi increases gradually from the core layer to the upper surface layer and the lower surface layer, the content of Pb decreases gradually, the content of Sr increases gradually, the content of Ca decreases gradually, and the content of Cu decreases gradually. The bismuth-based superconducting alloy has a symmetrical gradient structure, the core is rich in Cu to realize high current carrying, the surface layer is rich in Bi to improve the magnetic flux pinning ability, and the transition layer is arranged at the interface to realize gradual change of the composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of superconducting material preparation technology, specifically relating to a bismuth-based superconducting alloy and its preparation method. Background Technology

[0002] Bismuth-based high-temperature superconductors (such as Bi-2223 and Bi-2212) have significant advantages, including high critical temperatures (T_c) of 110K / 92K, operation in the liquid nitrogen temperature range, and low raw material costs, making them promising candidates for applications in superconducting magnets, current leads, magnetic shielding, and high-temperature superconducting power equipment. However, existing fabrication processes for bismuth-based superconducting alloys still face numerous bottlenecks, severely limiting their industrial application and performance improvement.

[0003] First, poor compositional uniformity is one of the main problems in existing preparation processes. In the traditional solid-state reaction method for preparing bismuth-based superconducting alloys, elements such as Bi, Pb, Sr, Ca, and Cu are prone to segregation, leading to an increase in impurity phases, disordered grain orientation, and weak grain boundary connections within the alloy. Ultimately, this results in a low critical current density (J_c), typically below 10 J_c at 77 K and 1 T. 4 A / cm² is insufficient to meet the current carrying capacity requirements of high-end applications.

[0004] Secondly, excessively high sintering temperatures bring a series of problems. Current processes typically use sintering temperatures between 850-900℃. High temperatures not only significantly increase energy consumption and raise the requirements for equipment materials, but also cause severe volatilization of Bi, leading to alloy composition deviations from design values, decreased purity of the superconducting phase, and further impacting superconducting performance. Simultaneously, high-temperature sintering easily causes deformation and cracking of the billet, reducing product yield.

[0005] Furthermore, existing bismuth-based superconducting alloys mostly employ homogeneous composition designs, failing to consider the different functional requirements of different parts, thus failing to achieve functional integration of high current carrying capacity in the core, high flux pinning on the surface, and high interfacial bonding. This homogeneous structure leads to rapid performance degradation of the alloy under magnetic field conditions, making it difficult to meet the application requirements under complex working conditions.

[0006] To address the aforementioned technical challenges, there is an urgent need to develop a method for preparing bismuth-based superconducting alloys that can achieve precise control of composition, reduce sintering temperature, improve superconducting performance, and keep costs under control, thereby promoting the industrial application of bismuth-based superconducting materials. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a bismuth-based superconducting alloy, which features high current carrying capacity in the core, high magnetic flux pinning on the surface, and high interfacial bonding strength.

[0008] The second objective of this invention is to provide a method for preparing bismuth-based superconducting alloys. This invention effectively solves the technical problems of poor compositional uniformity, high sintering temperature, severe Bi volatilization, and lack of functional gradient design by combining compositional gradient control with low-temperature sintering, thereby achieving low-energy consumption, low-cost, and high-performance preparation of bismuth-based superconducting alloys.

[0009] To achieve the above objectives, the present invention adopts the following technical solution:

[0010] This invention discloses a bismuth-based superconducting alloy, which has a symmetrical gradient structure from top to bottom consisting of an upper surface layer, an upper transition layer, a core layer, a lower transition layer, and a lower surface layer. From the core layer to the upper surface layer and from the core layer to the lower surface layer, the content of Bi increases sequentially, the content of Pb decreases sequentially, the content of Sr increases sequentially, the content of Ca decreases sequentially, and the content of Cu decreases sequentially.

[0011] The bismuth-based superconducting alloy provided by this invention has a symmetrical gradient structure. The core is Cu-rich to achieve high current carrying capacity, while the surface layer is Bi-rich to enhance flux pinning ability. A transition layer is set at the interface to achieve a gradual change in composition. Experiments have shown that the flux pinning ability of a superconductor mainly depends on its internal microscopic defects. In the Bi-2223 main phase, increasing the Bi content and decreasing the Pb content in the surface layer can induce the formation of nanoscale Pb-free or Bi-rich phase precipitates, resulting in numerous defects. These defects are key to improving the flux pinning force, while Pb has… The Pb content decreases from the core to the surface to stabilize the crystal structure and promote the formation of a high-critical-temperature superconducting phase. In the core, where current-carrying capacity is most critical, more Pb ensures the formation of a high-quality, high-purity Bi-2223 main phase. Sr ions have a larger radius, and increasing their content slightly alters the lattice parameters, introducing a stress field and inducing pinning centers. Therefore, the Sr content increases sequentially from the core to the surface to improve flux pinning performance. The Ca content is closely related to the carrier pool's ability to provide carriers. A Ca-rich core allows for the injection of more carriers into the CuO2 conductive layer, synergistically maximizing the carrier concentration on the CuO2 surface and thus enhancing current carrying capacity. A reduced Ca content on the surface, in conjunction with a Bi-rich strategy, modulates a localized electronic structure more favorable for flux pinning. This results in the bismuth-based superconducting alloy of this invention possessing integrated functions of high current carrying capacity in the core, high flux pinning on the surface, and high interfacial bonding.

[0012] In a preferred embodiment, the number of upper transition layers and lower transition layers is ≥1, preferably 1 to 2.

[0013] In a preferred embodiment, the chemical formula of the core layer is: Bi 1.7 Pb 0.3 Sr 1.9 Ca 2.1 Cu 3.1 O10+X1 Where X1 is +0.1~0.4, and the chemical formulas of both the upper and lower transition layers are: Bi 1.8 Pb 0.2 Sr 2.0 Ca 2.0 Cu 3.0 O 10+X2 , and / or Bi 1.9 Pb 0.1 Sr 2.1 Ca 1.9 Cu 2.9 O 10+X2 Where X2 is 0~0.2, and the chemical formula of both the upper and lower surface layers is Bi. 2.0 Pb 0.0 Sr 2.2 Ca 1.8 Cu 2.8 O 10+X3 , where X3 is -0.2 to 0.

[0014] Experiments have shown that controlling the chemical formula of the surface layer within the above range results in better performance. The core layer is rich in Cu / O, which is the superconducting current-carrying core and requires a sufficient number of hole carriers. The surface layer is relatively oxygen-deficient, which is conducive to the formation of defects or second-phase particles that can serve as flux pinning centers. The composition and oxygen content of the transition layer achieve a smooth transition from the core to the surface layer.

[0015] In a preferred embodiment, the bismuth-based superconducting alloy is a Bi-2223 phase, with a zero-resistance critical temperature T_c of 108-110K, and a critical current density J_c ≥ 2 × 10⁻⁶ under conditions of 77K and 1T. 4 A / cm², superconducting phase purity ≥95%.

[0016] This invention also provides a method for preparing a bismuth-based superconducting alloy, wherein surface precursor powder, transition layer precursor powder, and core layer precursor powder are spread in the order of lower surface layer, lower transition layer, core layer, upper transition layer, and upper surface layer, then pressed into a green blank, the green blank is sintered to obtain a sintered blank, and the sintered blank is subjected to annealing and oxygenation treatment in sequence to obtain the final product.

[0017] In the core layer precursor powder, transition layer precursor powder, and surface layer precursor powder, the content of Bi increases sequentially, the content of Pb decreases sequentially, the content of Sr increases sequentially, the content of Ca decreases sequentially, and the content of Cu decreases sequentially.

[0018] In this invention, firstly, core layer precursor powder, transition layer precursor powder, and surface layer precursor powder with specific compositional gradients are prepared, spread, and finally sintered to obtain a bismuth-based superconducting alloy with compositional gradient.

[0019] In a preferred embodiment, the chemical formula of the core layer precursor powder is: Bi 1.7 Pb 0.3 Sr 1.9 Ca 2.1 Cu 3.1 O 10 The chemical formula of the transition layer precursor powder is: Bi 1.8 Pb 0.2 Sr 2.0 Ca 2.0 Cu 3.0 O 10 , and / or Bi 1.9 Pb 0.1 Sr 2.1 Ca 1.9 Cu 2.9 O 10 The chemical formula of the surface precursor powder is Bi. 2.0 Pb 0.0 Sr 2.2 Ca 1.8 Cu 2.8 O 10 .

[0020] In a preferred embodiment, the preparation processes of the core layer precursor powder, transition layer precursor powder, and surface layer precursor powder are as follows: Bi2O3, PbO, SrCO3, CaCO3, and CuO are mixed according to the designed ratio and added to nitric acid to obtain a metal nitrate mixture. Oxalic acid solution is added dropwise to the metal nitrate mixture, and the pH value of the system is adjusted to 3.8-4.2 using ammonia water. The reaction yields a nano-sized oxalate coprecipitate, and the solid phase precipitate obtained by solid-liquid separation is spray-dried to obtain the final product.

[0021] This invention uses a co-precipitation-spray drying method to prepare nanoscale precursor powder, which improves elemental distribution uniformity by 60%, sintering activity by 40%, and reduces phase formation temperature by 100-150℃.

[0022] Further optimization resulted in Bi₂O₃, PbO, SrCO₃, CaCO₃, and CuO having a purity of ≥99.99%. The remaining materials used were analytical grade deionized water, oxalic acid, ammonia, and nitric acid as auxiliary materials.

[0023] Further preferably, the concentration of the metal nitrate mixture is 0.5-1.0 mol / L.

[0024] Further preferably, the concentration of the oxalic acid solution is 0.3-0.8 mol / L. In actual operation, the oxalic acid solution is slowly added dropwise while the pH of the system is adjusted to 4.0±0.2 with ammonia water. The reaction is stirred at room temperature to generate nano-sized oxalate coprecipitate.

[0025] Further optimization involves centrifugation as the solid-liquid separation method, with the centrifugation speed controlled at 3000-5000 r / min. In actual operation, after centrifugation, the sample is washed 3-4 times sequentially with deionized water and ethanol to remove impurities, and then dried in a vacuum drying oven at 80℃ for 12 hours to obtain a dried precipitate.

[0026] In a further preferred embodiment, the spray drying process involves feeding the solid precipitate into a spray dryer, setting the inlet temperature to 200-250℃ and the outlet temperature to 100-120℃. After drying, a nanoscale gradient precursor powder is obtained, which exhibits uniform elemental distribution and high sintering activity.

[0027] In a preferred embodiment, the particle size D50 of the core layer precursor powder, the transition layer precursor powder, and the surface layer precursor powder are all 50-200 nm, and the specific surface area is all 15-25 m² / g.

[0028] In a preferred embodiment, the powder spreading method is to spread the powder layer by layer, with the powder layer thickness being 50-200μm and the total thickness being 1-5mm; wherein the thickness of the upper and lower surface layers is 50-150μm, the thickness of the upper and lower transition layers is 50-150μm, and the thickness of the core layer is 0.7-4.7mm.

[0029] In this invention, a layer-by-layer powder spreading method is employed for three main reasons: first, it greatly alleviates interlayer stress and prevents cracking during sintering; second, it ensures that each layer is uniformly densified, resulting in a high-quality green body with no delamination, no cracks, and an overall density of 68%; and third, the layer-by-layer powder spreading creates numerous heterogeneous interfaces. At this diffusion distance, the combined highly active nano-precursor powder ensures a very thorough and uniform reaction during sintering.

[0030] In a preferred embodiment, the pressing molding is selected from one of cold isostatic pressing, compression molding, and co-firing, with cold isostatic pressing being the most preferred.

[0031] In a preferred embodiment, the pressing pressure is 200-300 MPa, and the holding time is 3-8 min.

[0032] The green body density is ≥65% of the theoretical density through pressing and molding, and the green body has no delamination or cracks, and the interlayer bonding is tight.

[0033] In a preferred embodiment, the sintering process is as follows: under an air atmosphere, the temperature is first raised to 450-550℃ at a heating rate of 1-5℃ / min and held for 2-3 hours. Then, the temperature is raised to 650-750℃, preferably 680-750℃, at a heating rate of 1-5℃ / min, while oxygen is introduced and the oxygen partial pressure is controlled at 0.1-0.5 MPa. The temperature is held for 2-6 hours, preferably 4 hours. Finally, under an oxygen-containing atmosphere with an oxygen partial pressure of 0.1-0.5 MPa, the temperature is lowered to 300-500℃ at a cooling rate of 0.5-3℃ / min, followed by furnace cooling to obtain the final product.

[0034] The sintering process of this invention first involves pre-sintering at 450-550℃ in an air atmosphere to remove carbon from the oxalate and allow the precursor powder to undergo a preliminary pre-reaction, generating the transition phase Bi-Sr-Ca-Cu-O, which lays the foundation for subsequent main sintering. Then, main sintering is carried out at 650-750℃. During this process, the Bi-2223 superconducting phase is fully generated and the green body is densified, with no liquid phase generated throughout, effectively reducing Bi volatilization. After the main sintering is completed, a slow cooling treatment is performed, maintaining an oxygen atmosphere throughout. The CuO2 surface carrier concentration is controlled by the slow cooling process to stabilize the superconducting phase structure and avoid cracks and performance degradation caused by excessively rapid cooling.

[0035] The final sintering temperature of this invention is ≤750℃, which is significantly lower than the traditional high-temperature sintering of 850-900℃. This effectively suppresses the volatilization of Bi element, making the volatilization amount of Bi element <1%.

[0036] In a preferred embodiment, the annealing treatment is carried out in a pure oxygen atmosphere with a purity ≥99.9%; the annealing temperature is 250-350℃, preferably 300℃; and the annealing time is 3-8 hours, preferably 6 hours. By placing the sintered billet into an annealing furnace for low-temperature annealing, grain boundary defects generated during sintering are effectively repaired, and the uniformity of oxygen content within the alloy is improved.

[0037] In a preferred embodiment, the oxygenation treatment is carried out under high-purity oxygen conditions, wherein the purity of the high-purity oxygen is ≥99.999%; the oxygenation treatment temperature is 100-250℃, preferably 200℃; the oxygenation treatment time is 10-13h, preferably 12h; and the pressure is 0.8-1.2 MPa, preferably 1 MPa. Through high-pressure oxygenation treatment, the oxygen content in the crystal lattice is further replenished, and the carrier concentration on the CuO2 surface is finely controlled, raising the critical temperature (T_c) to 108K-110K and increasing the critical current density (J_c) by more than 30%.

[0038] Beneficial effects

[0039] Compared with the prior art, the present invention has the following significant advantages:

[0040] 1. Significant leap in superconducting performance: Through three-dimensional compositional gradient design, a functional integration of high current carrying capacity in the core, high flux pinning on the surface, and high interfacial bonding was achieved. The resulting bismuth-based superconducting alloy is in the Bi-2223 phase, with a zero-resistance critical temperature T_c of 108-110K, and a critical current density J_c ≥ 2 × 10⁻⁶ under conditions of 77K and 1T. 4 With an A / cm², the magnetic flux pinning force is increased by 50%, and the J_c attenuation under a magnetic field is reduced by 40%, meeting the requirements of high-end superconducting applications.

[0041] 2. Significantly reduced production costs: The traditional high-temperature sintering of 850-900℃ is reduced to ≤750℃, reducing energy consumption by more than 50%; at the same time, low-temperature sintering effectively suppresses the volatilization of Bi element, with Bi volatilization of <1%, increasing raw material utilization by 20%, and eliminating the need for sintering equipment made of high-temperature alloy materials, reducing equipment investment by 30%.

[0042] 3. Improved composition uniformity and molding quality: The nano-scale precursor powder prepared by co-precipitation-spray drying method improves the element distribution uniformity by 60% and the sintering activity by 40%, which can reduce the phase formation temperature by 100-150℃; the gradient stacking + cold isostatic pressing process ensures that the green body is free of delamination and cracks, with tight interlayer bonding. After sintering, the density of the green body is ≥88% of the theoretical density, and the mechanical strength is improved by 50%.

[0043] 4. High feasibility for large-scale production: The process of this invention does not generate liquid phase or use highly toxic reagents. It is simple to operate, easy to control parameters, and has good stability. It can be directly scaled up to industrial production and is suitable for the preparation of various forms of bismuth-based superconducting alloys, such as wide strips, large-size bulk materials, and multi-core wires. Attached Figure Description

[0044] Figure 1 The present invention relates to a compositional gradient structure of a bismuth-based superconducting alloy.

[0045] Figure 2 The temperature-time curve of low-temperature segmented sintering in this invention.

[0046] Figure 3 SEM morphology image of the core layer precursor powder prepared in Example 1 of this invention.

[0047] Figure 4 Relationship between magnetization curve and J_c-magnetic field of superconducting alloy in Example 1 of this invention. Detailed Implementation

[0048] The present invention will be further described in detail below with reference to specific embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.

[0049] Example 1

[0050] A method for preparing bismuth-based superconducting alloys by controlling the composition gradient and low-temperature sintering, the specific steps of which are as follows:

[0051] (1) Gradient composition design: A three-dimensional gradient of Bi / Pb, Sr / Ca, and Cu / O is constructed along the material thickness, and a transition layer is set. The molar ratio of each layer is: core layer Bi 1.7 Pb 0.3 Sr 1.9 Ca 2.1 Cu 3.1 O 10+X Transition layer Bi 1.8 Pb 0.2 Sr 2.0 Ca 2.0 Cu 3.0 O 10+X Surface Bi 2.0 Pb 0.0 Sr 2.2 Ca 1.8 Cu 2.8 O 10+X ;

[0052] (2) Preparation of multiple precursors: Bi2O3, PbO, SrCO3, CaCO3 and CuO with a purity of 99.99% were selected and dissolved in nitric acid to prepare a 0.8 mol / L metal nitrate mixture; 0.5 mol / L oxalic acid solution was added dropwise, and the pH was adjusted to 4.0 with ammonia water to generate oxalate coprecipitate; after centrifugation, the mixture was washed three times with deionized water and ethanol, and vacuum dried at 80℃ for 12h; spray dried (inlet 220℃ / outlet 110℃) to obtain a gradient precursor powder with D50=120 nm and specific surface area of ​​20 m² / g;

[0053] (3) Gradient green body forming: The powder is spread layer by layer in the order of "surface layer → transition layer → core layer → transition layer → surface layer". The thickness of each layer is 100 μm. The thickness of the upper and lower surface layers is 100 μm, the thickness of the upper and lower transition layers is 100 μm, and the total thickness is 3 mm. Cold isostatic pressing is performed at a pressure of 250 MPa and a holding pressure at room temperature for 5 min. The green body density is 68% of the theoretical density. There is no delamination or cracks.

[0054] (4) Low-temperature segmented sintering: Under air atmosphere, the temperature is increased to 500℃ at 3℃ / min and held for 2h for pre-sintering; then the temperature is increased to 720℃ at 2℃ / min, oxygen is introduced, the oxygen partial pressure is controlled at 0.2 MPa, and the temperature is held for 4h for main sintering; 720℃→400℃ is cooled at 1℃ / min, 400℃→room temperature furnace cooling;

[0055] (5) Post-treatment: Annealing with pure oxygen at 300℃ for 6 hours, followed by oxygenation with high-purity oxygen at 200℃ and 1 MPa for 12 hours.

[0056] Performance testing: The obtained bismuth-based superconducting alloy is a Bi-2223 phase. Figure 4 The figure shows the relationship between the magnetization curve and the J_c-magnetic field of the superconducting alloy. The figure reveals a significant superconducting Meissner effect, with a zero-resistance temperature T_c reaching 109 K. The J_c-magnetic field curve shows that, under conditions of 77 K and 1 T, J_c is 2.5 × 10⁻⁶. 4 The J_c value is A / cm², and the J_c decays slowly with increasing magnetic field strength, indicating that the alloy has excellent flux pinning ability and magnetic field stability. In addition, the superconducting phase purity is 96% and the Bi volatilization is 0.8%.

[0057] The final composition of each layer is as follows: core layer Bi 1.7 Pb 0.3 Sr 1.9 Ca 2.1 Cu 3.1 O 10.2 Transition layer Bi 1.8 Pb 0.2 Sr 2.0 Ca 2.0 Cu 3.0 O 10.1 Surface Bi 2.0 Pb 0.0 Sr 2.2 Ca 1.8 Cu 2.8 O 9.9 ;

[0058] in Figure 3 This is a SEM image of the core precursor powder prepared in Example 1. The chemical formula of the precursor powder is Bi. 1.7 Pb 0.3 Sr 1.9 Ca 2.1 Cu 3.1 O 10 The powder particles are spherical or nearly spherical with a particle size D50 of 50-200 nm and are uniform, indicating that the co-precipitation-spray drying method can obtain nanoscale precursor powder with high dispersibility and high sintering activity.

[0059] Example 2

[0060] A method for preparing bismuth-based superconducting alloys by controlling the composition gradient and low-temperature sintering, the specific steps of which are as follows:

[0061] (1) Gradient composition design: A three-dimensional gradient of Bi / Pb, Sr / Ca, Cu / O is constructed along the radial direction of the material, and two transition layers are set. The molar ratio of each layer is: core layer Bi 1.7 Pb 0.3 Sr 1.9 Ca 2.1 Cu 3.1 O 10+XTransition layer Bi 1.8 Pb 0.2 Sr 2.0 Ca 2.0 Cu 3.0 O 10+X Bi 1.9 Pb 0.1 Sr 2.1 Ca 1.9 Cu 2.9 O 10+X Surface Bi 2.0 Pb 0.0 Sr 2.2 Ca 1.8 Cu 2.8 O 10+X ;

[0062] (2) Preparation of multiple precursors: Bi2O3, PbO, SrCO3, CaCO3 and CuO with a purity of 99.99% were selected and dissolved in nitric acid to prepare a 0.5 mol / L metal nitrate mixture; 0.5 mol / L oxalic acid solution was added dropwise, and the pH was adjusted to 3.8 with ammonia water to generate oxalate coprecipitate; after centrifugation, the mixture was washed 4 times with deionized water and ethanol, and vacuum dried at 80℃ for 12h; spray dried (inlet 220℃ / outlet 110℃) to obtain a gradient precursor powder with D50=80 nm and specific surface area of ​​25 m² / g;

[0063] (3) Gradient green body forming: Powder is spread layer by layer in the order of "surface layer → transition layer 1 → core layer → transition layer 2 → surface layer". The thickness of each layer is 50μm. The thickness of the upper and lower surface layers is 50μm, the thickness of the upper and lower transition layers is 50μm, and the total thickness is 1mm. Cold isostatic pressing is performed at a pressure of 200 MPa and a holding pressure at room temperature for 5 min. The green body density is 65% of the theoretical density. There is no delamination or cracks.

[0064] (4) Low-temperature segmented sintering: Under air atmosphere, the temperature is increased to 450℃ at 3℃ / min and held for 3h for pre-sintering; then the temperature is increased to 680℃ at 2℃ / min with oxygen partial pressure of 0.3 MPa and held for 6h for main sintering; 720℃→400℃ is cooled at 1℃ / min, and 400℃→room temperature furnace cooling.

[0065] (5) Post-treatment: Annealing with pure oxygen at 300℃ for 6 hours, followed by oxygenation with high-purity oxygen at 200℃ and 1 MPa for 12 hours.

[0066] Performance testing: The obtained bismuth-based superconducting alloy is a Bi-2223 phase, with T_c = 108 K and J_c = 2.2 × 10⁻⁶ K. 4 A / cm² (77K / 1T), superconducting phase purity 95%, Bi volatility 0.7%.

[0067] Example 3

[0068] A method for preparing bismuth-based superconducting alloys by controlling the composition gradient and low-temperature sintering, the specific steps of which are as follows:

[0069] (1) Gradient composition design: A three-dimensional gradient of Bi / Pb, Sr / Ca, Cu / O is constructed along the material thickness, and two transition layers are set, with the same molar ratio as in Example 2;

[0070] (2) Preparation of multiple precursors: Bi2O3, PbO, SrCO3, CaCO3 and CuO with a purity of 99.99% were selected and dissolved in nitric acid to prepare a 1.0 mol / L metal nitrate mixture; 0.5 mol / L oxalic acid solution was added dropwise, and the pH was adjusted to 4.2 with ammonia water to generate oxalate coprecipitate; after centrifugation, the mixture was washed three times with deionized water and ethanol, and vacuum dried at 80℃ for 12h; spray dried (inlet 220℃ / outlet 110℃) to obtain a gradient precursor powder with D50=150 nm and specific surface area of ​​15 m² / g;

[0071] (3) Gradient green body forming: The powder is spread layer by layer in the order of "surface layer → transition layer 1 → core layer → transition layer 2 → surface layer". The thickness of the upper and lower surface layers is 120 μm, the thickness of the upper and lower transition layers is 120 μm, the total thickness is 5 mm, and the thickness of the core layer is 200 μm. Cold isostatic pressing is performed at a pressure of 300 MPa, and the pressure is held at room temperature for 5 min. The green body density is 70% of the theoretical density, with no delamination and no cracks.

[0072] (4) Low-temperature segmented sintering: Under air atmosphere, the temperature is increased to 550℃ at 3℃ / min and held for 2h for pre-sintering; then the temperature is increased to 750℃ at 2℃ / min with oxygen partial pressure of 0.4 MPa and held for 2h for main sintering; 720℃→400℃ is cooled at 1℃ / min, and 400℃→room temperature furnace cooling.

[0073] (5) Post-treatment: Annealing with pure oxygen at 300℃ for 6 hours, followed by oxygenation with high-purity oxygen at 200℃ and 1 MPa for 12 hours.

[0074] Performance testing: The obtained bismuth-based superconducting alloy is a Bi-2223 phase, with T_c = 110 K and J_c = 2.8 × 10⁻⁶. 4 A / cm² (77K / 1T), superconducting phase purity 97%, Bi volatility 0.9%.

[0075] Comparative Example 1

[0076] Other conditions are the same as in Example 1, except that the gradient composition design is changed to a uniform composition design, that is, the surface layer, transition layer and core layer all use the same chemical formula Bi. 1.8 Pb 0.2 Sr 2.0 Ca 2.0 Cu 3.0 O10 The precursor powder was used, and the green body had a homogeneous single-layer structure. Results: The obtained alloy had T_c = 100K and J_c = 0.8 × 10⁻⁶ K. 4 A / cm² (77K / 1T), superconducting phase purity 82%. This indicates that the design without functional gradient cannot achieve the integration of high current carrying capacity in the core and magnetic flux pinning in the surface layer, and the performance degrades significantly under magnetic fields.

[0077] Comparative Example 2

[0078] Other conditions are the same as in Example 2, except that the two transition layers are removed, and the surface precursor powder (Bi) is directly applied. 2.0 Pb 0.0 Sr 2.2 Ca 1.8 Cu 2.8 O 10 ) and core precursor powder (Bi 1.7 Pb 0.3 Sr 1.9 Ca 2.1 Cu 3.1 O 10 Adjacent powder layers were laid. Result: Obvious cracks appeared at the interface after sintering, and J_c decreased to 0.5×10. 4 Below A / cm², the purity of the superconducting phase is only 78%. This indicates that without a transition layer, the large difference in composition between the core and the surface layer leads to interfacial thermal stress concentration and diffusion mismatch, severely impairing the superconducting performance.

[0079] Comparative Example 3

[0080] Other conditions were the same as in Example 3, except that the Ca content in the core layer precursor powder was reduced from 2.1 to 1.8 and the Cu content was reduced from 3.1 to 2.8 (i.e., the chemical formula of the core layer precursor powder was adjusted to Bi). 1.7 Pb 0.3 Sr 1.9 Ca 1.8 Cu 2.8 O 10 This exceeds the Cu- and Ca-rich range of the core layer in this invention. Result: T_c drops to 100K, J_c is only 1.2 × 10⁻⁶. 4 A / cm² (77K / 1T). This indicates that a Cu-rich and Ca-rich core is necessary to maintain a high carrier concentration, and an out-of-range Cu / Ca ratio will significantly reduce the alloy's current-carrying capacity.

Claims

1. A bismuth-based superconducting alloy, characterized in that: The bismuth-based superconducting alloy has a symmetrical gradient structure from top to bottom, consisting of an upper surface layer, an upper transition layer, a core layer, a lower transition layer, and a lower surface layer. From the core layer to the upper surface layer and from the core layer to the lower surface layer, the content of Bi increases sequentially, the content of Pb decreases sequentially, the content of Sr increases sequentially, the content of Ca decreases sequentially, and the content of Cu decreases sequentially.

2. The bismuth-based superconducting alloy according to claim 1, characterized in that: The chemical formula of the core layer is: Bi 1.7 Pb 0.3 Sr 1.9 Ca 2.1 Cu 3.1 O 10+X1 Where X1 is +0.1~0.4, and the chemical formulas of both the upper and lower transition layers are: Bi 1.8 Pb 0.2 Sr 2.0 Ca 2.0 Cu 3.0 O 10+X2 , and / or Bi 1.9 Pb 0.1 Sr 2.1 Ca 1.9 Cu 2.9 O 10+X2 Where X2 is 0~0.2, and the chemical formula of both the upper and lower surface layers is Bi. 2.0 Pb 0.0 Sr 2.2 Ca 1.8 Cu 2.8 O 10+X3 , where X3 is -0.2 to 0.

3. The bismuth-based superconducting alloy according to claim 1, characterized in that: The bismuth-based superconducting alloy is in the Bi-2223 phase, with a zero-resistance critical temperature T_c of 108-110K, and a critical current density J_c ≥ 2 × 10⁻⁶ K under conditions of 77K and 1T. 4 A / cm², superconducting phase purity ≥95%.

4. A method for preparing a bismuth-based superconducting alloy according to any one of claims 1-3, characterized in that: The surface precursor powder, transition layer precursor powder, and core layer precursor powder are spread in the order of lower surface layer, lower transition layer, core layer, upper transition layer, and upper surface layer. Then, the powder is pressed into shape to obtain a green body. The green body is sintered to obtain a sintered body. The sintered body is then subjected to annealing and oxygenation treatment in sequence to obtain the final product. In the core layer precursor powder, transition layer precursor powder, and surface layer precursor powder, the content of Bi increases sequentially, the content of Pb decreases sequentially, the content of Sr increases sequentially, the content of Ca decreases sequentially, and the content of Cu decreases sequentially.

5. The method for preparing a bismuth-based superconducting alloy according to claim 4, characterized in that: The chemical formula of the core layer precursor powder is: Bi 1.7 Pb 0.3 Sr 1.9 Ca 2.1 Cu 3.1 O 10 The chemical formula of the transition layer precursor powder is: Bi 1.8 Pb 0.2 Sr 2.0 Ca 2.0 Cu 3.0 O 10 , and / or Bi 1.9 Pb 0.1 Sr 2.1 Ca 1.9 Cu 2.9 O 10 The chemical formula of the surface precursor powder is Bi. 2.0 Pb 0.0 Sr 2.2 Ca 1.8 Cu 2.8 O 10 .

6. The method for preparing a bismuth-based superconducting alloy according to claim 4, characterized in that: The preparation processes of the core layer precursor powder, transition layer precursor powder, and surface layer precursor powder are as follows: Bi2O3, PbO, SrCO3, CaCO3, and CuO are mixed according to the designed ratio and added to nitric acid to obtain a metal nitrate mixture. Oxalic acid solution is added dropwise to the metal nitrate mixture, and then the pH value of the system is adjusted to 3.8-4.2 using ammonia water. The reaction yields nano-sized oxalate coprecipitate, and the solid phase precipitate obtained by solid-liquid separation is spray-dried to obtain the final product. The purity of Bi2O3, PbO, SrCO3, CaCO3, and CuO is ≥99.99%; The concentration of the metal nitrate mixture is 0.5-1.0 mol / L; The concentration of the oxalic acid solution is 0.3-0.8 mol / L; The solid-liquid separation method is centrifugation, and the centrifugation speed is controlled at 3000-5000 r / min during the centrifugation process; The spray drying process involves feeding the solid precipitate into a spray dryer, setting the inlet temperature to 200-250℃ and the outlet temperature to 100-120℃. The particle size D50 of the core layer precursor powder, the transition layer precursor powder, and the surface layer precursor powder are all 50-200 nm, and the specific surface area is all 15-25 m² / g.

7. The method for preparing a bismuth-based superconducting alloy according to claim 4, characterized in that: The powder spreading method is to spread the powder layer by layer, with a powder layer thickness of 50-200μm and a total thickness of 1-5 mm; The thickness of the upper and lower surface layers is 50-150 μm, the thickness of the upper and lower transition layers is 50-150 μm, and the thickness of the core layer is 0.7-4.7 mm.

8. The method for preparing a bismuth-based superconducting alloy according to claim 4, characterized in that: The compression molding is selected from one of cold isostatic pressing, compression molding, and co-extrusion molding. The pressing pressure is 200-300 MPa, and the holding time is 3-8 min.

9. The method for preparing a bismuth-based superconducting alloy according to claim 4, characterized in that: The sintering process is as follows: Under an air atmosphere, the temperature is first raised to 450-550℃ at a heating rate of 1-5℃ / min and held for 2-3 hours. Then, the temperature is raised to 650-750℃ at a heating rate of 1-5℃ / min, and oxygen is introduced while controlling the oxygen partial pressure to 0.1-0.5 MPa. The temperature is held for 2-6 hours. Finally, under an oxygen-containing atmosphere with an oxygen partial pressure of 0.1-0.5 MPa, the temperature is lowered to 300-500℃ at a cooling rate of 0.5-3℃ / min, followed by furnace cooling to obtain the final product.

10. The method for preparing a bismuth-based superconducting alloy according to claim 4, characterized in that: The annealing process is carried out in a pure oxygen atmosphere with a purity ≥ 99.9%; the annealing temperature is 250-350℃ and the annealing time is 3-8h. The oxygenation treatment is carried out under high-purity oxygen conditions, wherein the purity of the high-purity oxygen is ≥99.999%; the oxygenation treatment temperature is 100-250℃, the oxygenation treatment time is 10-13h, and the pressure is 0.8-1.2 MPa.